Relationship Between Thermal Aging and Insulation Properties of XLPE - Lihua ZHAO; Lan YANG; Weiwei LI; Weiqing WU; Junwen REN (Zhongguo dianli)
In order to study the crossed-linked polyethylene (XLPE) insulation material in thermal decomposition activation energy, electrical and mechanical properties changing with thermal aging degree, accelerated thermal aging tests were carried out at 110 ℃ on XLPE insulation material for AC cables. The thermal decomposition behavior of XLPE at 20~600 ℃ was studied by thermogravimtric analyzer (TGA) test. The electrical properties of the aged XLPE samples were studied by AC breakdown testing, broadband dielectric spectrum testing and volume resistivity testing; and the mechanical properties of the aged XLPE samples were studied by tensile test. The results show that the crosslinking structure and crystalline state of XLPE are destroyed by thermal aging, and the activation energy of XLPE tends to decrease. Due to the rapid oxidation reaction, the XLPE molecular chain breaks and the cross-linking structure weakens, resulting in serious deterioration of XLPE insulation materials. The activation energy, breakdown strength, volume resistivity, elastic modulus and elongation at break tend to decrease with the increase of aging time, while the dielectric constant, dielectric loss and conductivity tend to increase.